Elektrochemisch-optische Impedanzspektroskopie - Manka, Daniel (Schriften des Instituts für Angewandte Materialien - Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Angewandte Materialien - Werkstoffe der Elektrotechnik, 2016)
This book introduces a new method to develop electrode models. The method is based on electrical impedance measurements combined with dynamic reflection and transmission measurements from the electrode surface. The implementation of an electrochemical-optical model allows advanced model validation. The method is applied exemplary to a graphite anode and a redox-polymer electrode, which is leading to highly detailed electrode models.